A taxonomic study of the genus Tetra Keifer (Acari: Eriophyidae: Phyllocoptinae: Anthocoptini) from Shaanxi Province, China with descriptions of nine new species - Xue, Xiao-Feng; Song, Zi-Wei; Hong, Xiao-Yue (Zootaxa, 2006)
Nine new species of the genus Tetra Keifer (Acari: Eriophyidae: Anthocoptini) from Shaanxi Province, northwestern China are described and illustrated, namely Tetra louguantais sp. nov. on Pistacia chinensis Bunge (Anacardiaceae); Tetra pinnatifidae sp. nov. on Crataegus pinnatifida Bunge (Rosaceae); Tetra sorbusis sp. nov. on Sorbus sp. (Rosaceae); Tetra acerii sp. nov. on Acer sp. (Aceraceae); Tetra smilaxis sp. nov. on Smilax china L. (Liliaceae); Tetra lucidi sp. nov. on Ligustrum lucidum Ait. (Oleaceae); Tetra ningshanis sp. nov. and Tetra cuihuae sp. nov. on Populus sp. (Salicaceae); and Tetra salixis sp. nov. on Salix babylonica L. (Salicaceae). All species described here are vagrant on the undersurface of host leaves.